FACTORS AFFECTING THE INTENTION TO QUIT FROM THE TEACHING PROFESSION AMONG VOCATIONAL TEACHERS - Sukritta Preechawong; Anusit Anmanatrakul; Pichet Pinit; Ravinder Koul (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
This paper aimed to explore the variables that influenced the intention to quit the teaching profession among vocational teachers. Moreover, the researchers examined the differences in the perception of the levels of emotional exhaustion, depersonalization, personal accomplishment, job satisfaction, and life satisfaction among vocational teachers in Thailand. The target population comprised vocational teachers from public colleges in Thailand with a total number of 29,915. The stratified random sampling technique was used for selecting the samples. The data collection involved self-report surveys from 510 vocational teachers from 55 vocational colleges in Thailand's metropolitan, north, northeast, east, and south. Correlation and regression analyses were used to examine the possible relationships among the variables and identify the significant variables. The findings reported that emotional exhaustion and depersonalization were moderate while personal accomplishment was at a high level. Job satisfaction was the strongest predictor of the intention to quit. In addition, three components of burnout influenced the intention to quit among the vocational teachers: emotional exhaustion, depersonalization, and personal accomplishment. For the implication, this study recommended a practical application in the dimension of policy improvement concerning teachers' welfare. It emphasized the need to develop programs supporting teachers' mental health to reduce burnout and increase job satisfaction.